Nursing interventions for the prevention of peristomal dermatitis in intestinal stomas: A systematic review (Research, Society and Development, 2021)
Introduction: Despite advances in surgical techniques for making and caring for people with stomas, peristomal dermatitis of intestinal stomata is frequent. In this context, nursing plays a fundamental role in preventing these complications. Objective: To carry out a systematic review to identify nursing interventions used as preventive measures for peristomal dermatitis in intestinal ostomies. Method: A systematic review was carried out in the Scopus, PubMed (MEDLINE), Cochrane Library, Web of Science and CINAHL databases. Randomized controlled trials investigating the effectiveness of nursing interventions in preventing peristomal dermatitis, published in English, Portuguese and Spanish until December 2020, were selected. Results: Initially, 2,976 studies were identified, however only three of these were included in the final sample, which were published between 2011 and 2017. Prevention actions found in clinical trials were about educational measures, use of moldable skin barrier and standardization of cleaning technique and use of hydrocolloid powder as prevention. Conclusion: Evidence on nursing interventions in the preventive care of peristomal injuries is still scarce and with considerable risk of bias. Thus, the scientific community is encouraged to carry out primary studies of high methodological rigor, in order to support the practice of stomatherapy and promote quality care based on the best scientific evidence.